State of art of real-time singing voice synthesis - Brum, Leonardo; Moreno, Edward David (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
This paper describes the state of art of realtime singing voice synthesis and presents its concept, applications and technical aspects. A technological mapping and a literature review are made in order to indicate the latest developments in this area. We made a brief comparative analysis among the selected works. Finally, we have discussed challenges and future research problems. Keywords: Real-time singing voice synthesis, Sound Synthesis, TTS, MIDI, Computer Music.